PENGARUH FAKTOR PRODUKSI TERHADAP PENDAPATAN PEMETIK DAUN KAYU PUTIH - Hendro Prahasto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Leaf cutting activity gave contribution to the total income of cajuput leaf cutters with an average of Rp.162,000 per year or approximately 41% of the total income. The result of linear regression analysis shows that the income from cajuput leaf cutting gave a significant income contribution to the leaf cutters total income.Based on the result of Cobb-Douglas analysis, it is shown that four production variables i.e. share area (Xl), work time spent outside the leaf cutting activity (X2), work time spent for leaf cutting activity (X3), and capital or farming production cost (X4) gave a significant impact on the total income of leaf cutters. The production function: equation isIn Y = 3.5385+0.1189 In XI + 0.0283 In X2 + 0.2976 In X3 + 0.1255 In X4 + E with determination coefficient (R2) of 0.7549.